T-Shaped Professionals : Adaptive Innovators. - Moghaddam, Yassi (Service systems and innovations in business and society collection., 2018)
This book provides a wide range of perspectives around the thesis that going forward the world will need more T-Shaped Professionals who are adaptive innovators. Skills are one of the hallmarks of every profession. The skills of doctors allow them to heal others, while the skills of lawyers allow them to seek justice for others. What types of skills should adaptive innovators possess? More specifically, what types of skills should future-ready adaptive innovators have to allow them to thrive in the age of accelerating change? We invite the reader to explore this question from the perspective of individuals, educators, practitioners, and those in government, as well as those trying to measure more precisely just what it means to be a T-Shaped Professional and adaptive innovator.